2023
DOI: 10.1177/08850666231166344
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated with Severity and Death from COVID-19 in Iran: A Systematic Review and Meta-Analysis Study

Abstract: Objectives: This study aims to investigate the risk factors associated with severity and death from COVID-19 through a systematic review and meta-analysis of the published documents in Iran. Methods: A systematic search was performed based on all articles indexed in Scopus, Embase, Web of Science (WOS), PubMed, and Google Scholar in English and Scientific Information Database (SID) and Iranian Research Institute for Information Science and Technology (IRA)NDOC indexes in Persian. To assess quality, we used the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 106 publications
0
0
0
Order By: Relevance
“…This study was the first to investigate the factors associated with 30-day mortality in COVID-19 patients in Indonesia. This study found that the severity of the COVID-19 infection is a major risk factor for 30-day mortality, similar to other studies [20][21][22]. Also, this finding is similar to other infections, such as pneumonia, sepsis, and meningitis, where the more severe the infection is, the higher the likelihood for complications and mortality.…”
Section: Discussionsupporting
confidence: 90%
“…This study was the first to investigate the factors associated with 30-day mortality in COVID-19 patients in Indonesia. This study found that the severity of the COVID-19 infection is a major risk factor for 30-day mortality, similar to other studies [20][21][22]. Also, this finding is similar to other infections, such as pneumonia, sepsis, and meningitis, where the more severe the infection is, the higher the likelihood for complications and mortality.…”
Section: Discussionsupporting
confidence: 90%
“…The findings of this study provide supporting evidence in line with existing guidelines, suggesting that the presence of dyspnea and low SPO2 levels at admission, as well as the presence of extensive pneumonia observed on thorax CT scans, are associated with severe disease in patients diagnosed with COVID-19 pneumonia [2,10]. In a meta-analysis that included the evaluation of 69 studies [11], a significant association was found between the symptoms of dyspnea and mortality. Similarly, in our study, we observed a significant increase in dyspnea as a presenting symptom among patients with severe disease (p=0.005).…”
Section: Discussionsupporting
confidence: 87%
“…Similarly, in our study, we observed a significant increase in dyspnea as a presenting symptom among patients with severe disease (p=0.005). While advanced age, male gender, and the presence of hypertension, diabetes, and cardiovascular comorbidities are known risk factors for severe disease and mortality in COVID-19 [10][11][12][13]. Incompatible with the literature, no significant differences were observed between the two groups in terms of gender, age, and comorbidities in this study.…”
Section: Discussionsupporting
confidence: 62%
“…However, the infection of SARS-CoV-2 has resulted in millions of deaths worldwide and seriously threatened human health in the last 3 years. Studies have shown that COVID-19-related death is signi cantly associated with chronic diseases like diabetes, hypertension, cardiovascular disease, cerebrovascular disease, and chronic kidney disease [3].…”
Section: Introductionmentioning
confidence: 99%